Insurance Versus Moral Hazard in Income-Contingent Student Loan Repayment - de Silva, Tim (Quarterly Journal of Economics, 2025)
Abstract Student loans with income-contingent repayment insure borrowers against income risk but can reduce their incentives to earn more. Using a change in Australia’s income-contingent repayment schedule, I show that borrowers reduce their labor supply to lower their repayments. These responses are larger among borrowers with more hourly flexibility, a lower probability of repayment, and tighter liquidity constraints. I use these responses to estimate a dynamic model of labor supply with frictions that generate imperfect adjustment. My estimates imply that the labor supply responses to income-contingent repayment limit the optimal amount of insurance in government-provided student loans. However, these responses are too small to justify fixed-repayment contracts: restructuring existing student loans from fixed repayment to a constrained-optimal income-contingent loan—while keeping the tax and transfer system unchanged—increases borrower welfare by the equivalent of a 0.8% increase in lifetime consumption at no additional fiscal cost.